A Portrait-Corpus Study of Language Attitudes towards Afrikaans and English. Issue 2 (4th May 2021) - Coetzee-Van Rooy, Susan; Peters, Arne
Abstract: Language portraits are useful instruments to elicit speakers' reflections on the languages in their repertoires. In this study, we implement a "portrait-corpus approach" (Peters and Coetzee-Van Rooy 2020) to investigate the conceptualisations of the languages Afrikaans and English in 105 language portraits. In this approach, we use participants' reflections about their placement of the two languages on a human silhouette as a linguistic corpus. Relying on quantitative and qualitative analyses using WordSmith, Statistica and Atlas.ti, our study shows that Afrikaans is mainly conceptualised as a language that is located in more peripheral areas of the body (for example, the hands and feet) and, hence, is perceived as less important in participants' repertoires. The central location of English in the head reveals its status as an important language in the participants' multilingual repertoires. We argue that these conceptualisations of Afrikaans and English provide additional insight into the attitudes towards these languages in South Africa.